The auction = 爱的拍卖 - Lim, Zhong Wei (Nanyang Technological University, 2021)
Failure to escape a marriage proposal from her longtime partner, Gloria is forced to choose contentment over ambition. The Restaurant transforms into the auction where the bids represents the ambitions Gloria have for her life. We follow Gloria's decisions as the auction goes on, revealing her true desires.